Captopril to mitigate chronic renal failure after hematopoietic stem cell transplantation: a randomized controlled trial - Cohen, Eric P (2007)
PURPOSE: Chronic renal failure is an acknowledged complication of hematopoietic stem cell transplantation (HSCT) in humans. It can be caused in part by radiation injury when HSCT is preceded by sufficient total body irradiation (TBI). Studies in laboratory animals show the benefit of angiotensin converting enzyme (ACE) inhibitors in mitigation and treatment of this complication. We thus conducted a randomized controlled trial testing whether the ACE inhibitor captopril was effective in mitigating chronic renal failure after HSCT. METHODS AND MATERIALS: 55 subjects undergoing TBI-HSCT were enrolled. Captopril, or identical placebo, was started at engraftment, and continued as tolerated until one year after HSCT. RESULTS: The baseline serum creatinine and calculated glomerular filtration rate (GFR) did not differ between groups. The one-year serum creatinine was lower, and the GFR higher, in the captopril compared to the placebo group ( p=0.07, for GFR). Patient survival was higher in the captopril compared to the placebo group, but this was also not statistically significant (p=0.09). In study subjects who were on study drug for more than two months, the one-year calculated GFRs were 92 ml/min and 80 ml/min, for the captopril and placebo groups, respectively (p=0.1). There was no adverse effect on hematological outcome. CONCLUSION: We conclude that there is a trend in favor of captopril in mitigation of chronic renal failure after radiation-based HSCT.